2022
DOI: 10.1055/a-1933-2847
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of Clinically Significant Portal Hypertension in Patients with Liver Cirrhosis: The Role of Contrast-Enhanced Ultrasound Perfusion Imaging and Elastography

Abstract: Background Hepatic venous pressure gradient (HVPG) is the gold standard for assessing the degree of portal hypertension (PH), but it is not suitable for routine clinical use. The recently developed ultrasonography techniques, dynamic contrast-enhanced ultrasound (D-CEUS) and liver stiffness (LS), have expanded the possibilities for noninvasive evaluation. Aims To investigate the usefulness of D-CEUS and elastographic parameters in assessing the presence and degree of PH.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Our ndings suggest that an early blood pressure drop may serve as a more accessible and cost-effective predictor of prognosis than more complex measurements such as HVPG. Early peak blood pressure drop measurements are readily available in clinical practice and can provide valuable information for risk strati cation and prognostic assessment [23]. Additionally, several studies have indicated that poorer baseline renal function and acute kidney injury (AKI) are independently associated with a poorer prognosis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings suggest that an early blood pressure drop may serve as a more accessible and cost-effective predictor of prognosis than more complex measurements such as HVPG. Early peak blood pressure drop measurements are readily available in clinical practice and can provide valuable information for risk strati cation and prognostic assessment [23]. Additionally, several studies have indicated that poorer baseline renal function and acute kidney injury (AKI) are independently associated with a poorer prognosis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…An objective and quantitative diagnosis of perfusion characteristics is of particular relevance in the follow-up of cancer patients but can also be used for the diagnostic assessment of other pathological changes associated with alterations in tissue perfusion. This applies, for example, to the noninvasive diagnosis of the progression of parenchymal liver disease, liver cirrhosis, and portal hypertension [10,11,12,13,14,15,16] and for the noninvasive evaluation of chronic kidney disease [17,18,19] and subclinical kidney transplant rejection [17,20,21,22,23,24]. There are partially contradictory data regarding the evaluation of inflammatory activity and response to biologic therapy in inflammatory bowel disease [25,26,27,28,29,30,31,32,33,34].…”
Section: Why Do We Need Quantification?mentioning
confidence: 99%